A comparative study to investigate the level of cognitive impairment among epileptic and psychogenic non-epileptic patients - Noreena Kausar; Hafsa Qurban; Bushra Bibi (Journal of the Pakistan Medical Association, 2020)
Objective: To compare cognitive impairment between patients having epileptic seizures and those having psychogenic non-epileptic seizures. Methods: The cross-sectional study was conducted from May to November 2016 in Jhelum, Pakistan, and comprised epileptic and psychogenic non-epileptic patients who were selected from different psychiatric units of the city. Bender Gestalt Test-II was administered to check the cognitive impairment of participants. Data was analysed using SPSS 21. Results: Of the 125 subjects, 62(49.6%) were epileptic and 63(50.4%) were psychogenic non-epileptic patients. Psychogenic non-epileptic patients performed better compared to epileptic patients (p?.001). The effect size of the finding was 0.42, indicating medium size effect. Conclusion: Epileptic patients were found to have more cognitive impairment than psychogenic non-epileptic patients. Key Words: Cognitive impairment, Epileptic, Psychogenic non-epileptic, Seizures, Continuous...